Costs and benefits of trade shocks: Evidence from Chilean local labor markets - Andrés César; Guillermo Falcone; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
We study Chile's labor market responses to trade shocks during 1996-2006, exploiting spatial and time variations in trade exposure arising from initial differences in industry specialization across local labor markets and the evolution of shocks across industries. We take advantage of China's supply and demand's worldwide shocks to instrument for Chinese import competition and demand for Chilean exports. Our main finding is that increasing manufacturing import competition implied a significant rise in labor informality in more exposed local markets, especially among young and unskilled workers. These groups also suffered significant relative wage losses. Meanwhile, locations that benefited most from the increased demand for primary products experienced a relative increase in employment, particularly among young individuals, and reallocation from self-employment towards salaried jobs in the formal sector, along with relative wage gains among old-age workers. Interestingly, these areas experienced a smaller increase in tertiary education enrollment rates than less exposed areas.
Keywords: F14; F16; J23; J31; L60; O17; Q02; R12; R23; 330; Trade Shocks; Local Labor Markets; Employment; Informality; Chile